Barriers Broken: Genetic swamping in restored Brook Trout populations - Rebecca J. Smith; Matt A. Kulp; Benjamin M. Fitzpatrick (PLoS ONE, 2025)
Scientists use reintroductions to restore native species to their historical ranges but sometimes overlook effects of dispersal on genetic structure of restored populations. Unidirectional or biased gene flow can result in genetic swamping, where unique variation in a recipient population is replaced by genotypes from the source population. In theory, this can result in loss of advantageous alleles and adaptive capacity. In Great Smoky Mountains National Park native Brook Trout ( Salvelinus fontinalis) are being restored to streams from which they had been extirpated. Multiple source lineages are mixed in restoration sites to maximize genetic diversity. However, in our study system, translocated fish were released unevenly along a rugged mountain stream, resulting in an upstream population coming from only one source stock and a downstream population that was a mixture of three source stocks. A natural cascade allows downstream dispersal but prevents or constrains upstream movement. Theory predicts that such biased movement will lead to genetic swamping, i.e., reduction or loss of representation of ancestral lineages released only in the downstream population. However, the rate of gene flow and degree of asymmetry were unknown. Here, we used genetic and population density data to confirm the directionality of dispersal, estimate the rate of genetic swamping, and assess alternative mitigation strategies. Our results indicate that the downstream population has already become dominated by ancestry from the upstream source and translocation from within the restored stream will not achieve the intended genetic diversity. Instead, introducing additional fish from the original source stocks above the natural barrier would be necessary to equalize the contribution of all three source populations. Our results emphasize the importance of understanding the interplay between dispersal and genetic structure for conservation planning.